PENCEGAHAN PERNIKAHAN DINI USIA REMAJA - Rezkillah, Inang Irma; Ramdhan, Saidah; Kasturi, Kasturi; Komalasari, Ayu; Julianti, Julianti; Azizah, Fadila; Nurfadillah, Nurfadillah; Riansyah, Riansyah (Jurnal Abdi Insani, 2024)
Early marriage in Indonesia, especially in rural areas, is a serious issue that negatively affects the health and education of the younger generation. The government's free education program aims to create a golden generation, but the high rate of early marriage hinders the achievement of this goal. This study identifies factors that influence early marriage, such as knowledge, education level and family economic conditions. Through socialization activities at Darul Hamidin Junior High School in Padamara, East Lombok, the author sought to increase students' understanding of the dangers of early marriage. Lecture and discussion methods were used to deliver material related to the negative impact of early marriage, with the aim of raising awareness and motivating adolescents to stay away from the practice. The results of the socialization showed an increase in students' understanding after the activity. This research emphasizes the need for collaborative efforts from various elements of society to reduce the number of early marriages and support a more qualified generation to achieve national education goals.